What Is the Future of AI-Powered Virtual Care? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2025)
The healthcare landscape is undergoing a paradigm shift, driven by the rapid evolution of digital technologies. Among these, Artificial Intelligence (AI) is ...
Keywords: Telemedicine and Digital Health; Future; AI-Powered; Virtual; Artificial Intelligence; Healthcare; Patient Care